Gas Sensing Mechanism and Adsorption Properties of C2H4 and CO Molecules on the Ag3–HfSe2 Monolayer: A First-Principle Study - Jia, Lufen; Chen, Jianxing; Cui, Xiaosen; Wang, Zhongchang; Zeng, Wen; Zhou, Qu (Frontiers in Chemistry, 2022)
The detection of dissolved gases in oil is an important method for the analysis of transformer fault diagnosis. In this article, the potential-doped structure of the Ag3 cluster on the HfSe2 monolayer and adsorption behavior of CO and C2H4 upon Ag3–HfSe2 were studied theoretically. Herein, the binding energy, adsorption energy, band structure, density of state (DOS), partial density of state (PDOS), Mulliken charge analysis, and frontier molecular orbital were investigated. The results showed that the adsorption effect on C2H4 is stronger than that on CO. The electrical sensitivity and anti-interference were studied based on the bandgap and adsorption energy of gases. In particular, there is an increase of 55.49% in the electrical sensitivity of C2H4 after the adsorption. Compared to the adsorption energy of different gases, it was found that only the adsorption of the C2H4 system is chemisorption, while that of the others is physisorption. It illustrates the great anti-interference in the detection of C2H4. Therefore, the study explored the potential of HfSe2-modified materials for sensing and detecting CO and C2H4 to estimate the working state of power transformers.